The Impact of Electronic Money Use on the Quality of Accounting - Abdelwhab Mahmoud Jadaan Rawashdeh (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2017)
The definition o f the term “electronic m oney” was analyzed. The use o f electronic money in the context o f its consideration in international accounting was studied. The basic theoretical andpractical issues, which arise in accounting while displaying operations o f the presence and movement o f electronic money, were revealed. The priority areas to improve the methods o f accounting payment transactions between counterparties when using electronic money were identified. The impact o f electronic money on the quality o f international accounting was outlined.